Three Medicago MtFUL genes have distinct and overlapping expression patterns during vegetative and reproductive development and 35S:MtFULb accelerates flowering and causes a terminal flower phenotype in Arabidopsis - Jaudal, Mauren; Zhang, Lulu; Che, Chong; Putterill, Joanna (Frontiers in Genetics, 2015)
The timing of the transition to flowering is carefully controlled by plants in order to optimise sexual reproduction and the ensuing production of seeds, grains and fruits. The genetic networks that regulate floral induction are best characterised in the temperate eudicot Arabidopsis in which the florigen gene FT plays a major role in promoting the transition to flowering. Legumes are an important plant group, but less is known about the regulation of their flowering time. In the model legume Medicago truncatula (Medicago), a temperate annual plant like Arabidopsis, flowering is induced by prolonged cold (vernalisation) followed by long day lengths (LD). Recent molecular-genetic experiments have revealed that a FT-like gene, MtFTa1, is a central regulator of flowering time in Medicago. Here, we characterize the three Medicago FRUITFULL (FUL) MADS transcription factors, MtFULa, MtFULb and MtFULc using phylogenetic analyses, gene expression profiling through developmental time courses, and functional analyses in transgenic plants. MtFULa and MtFULb have similarity in sequence and expression profiles under inductive environmental conditions during both vegetative and reproductive development while MtFULc is only up regulated in the apex after flowering in LD conditions. Sustained up regulation of MtFULs requires functional MtFTa1 but their transcript levels are not affected during cold treatment. Overexpression of MtFULa and MtFULb promotes flowering in transgenic Arabidopsis plants with an additional terminal flower phenotype on some 35S:MtFULb plants. An increase in transcript levels of the MtFULs was also observed in Medicago plants overexpressing MtFTa1. Our results suggest that the MtFULs are targets of MtFTa1. Overall, this work highlights the conserved functions of FUL-like genes in promoting flowering and other roles in plant development and thus contributes to our understanding of the genetic control of the flowering process in Medicago.